Effects of Economic Conditions and Organizational Structure on Local Health Jurisdiction Revenue Streams and Personnel Levels in Connecticut, 2005-2012. - Pallas, Sarah Wood; Kertanis, Jennifer; O'Keefe, Elaine; Humphries, Debbie L (Public health reports (Washington, D.C. : 1974), 2015)
We investigated whether or not changes in economic conditions during the 2008-2010 U.S. recession were associated with changes in Connecticut local health jurisdictions' (LHJs') revenue or personnel levels.